Relationship between Burnout, Quality of Life, and Work Ability Index—Directions in Prevention - Mirjana Arandjelovic; Maja Nikolic; Slavisa Stamenkovic (The Scientific World Journal)
The aim of our study was (1) to test the possibilities of standardized questionnaires for burnout, quality of life, and work ability in Serbia by investigating interactions of these phenomena in food manufacturing workers in Serbia; and (2) to determine possible preventive measures. The study enrolled 489 food manufacturing workers in the region of Niš (Serbia) during the period from January 2008 to February 2009. We included three standardized questionnaires: for burnout (CBI), quality of life (ComQoL-A5), and the work ability index (WAI) in the Serbian language. The results of our study indicate high scores in personal (60.0) and work burnout (67.9), lower scores for objective (66.2%SM) and subjective quality of life in enrolled subjects (69.2%SM), and an excellent work ability index in most workers (65.8%). The questionnaires tested are reliable instruments in the Serbian region. Burnout, quality of life, and work ability are significantly interrelated categories in food manufacturing workers. There is a high degree of work burnout that has not yet been accompanied with significant impairment of quality of living and work ability in exposed workers. That is why a salutogenic approach in the prevention of this phenomenon, by health-promotion programs in the workplace, would be the method of choice for burnout improvement.